The Application of Risk Management in Organizing Sports Activities in Schools - Muhammad Syaleh (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2025)
The implementation of sports activities in schools, although essential for the physical and character development of students, carries various potential risks, ranging from physical injuries to organizational and financial problems. This study aims to analyze the implementation of risk management in the organization of sports activities in schools in Gajahmungkur District, Semarang City. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews with physical education teachers, principals, and students, as well as participatory observation and documentation studies. The results show that awareness of the importance of risk management still varies between schools. Some schools have implemented ad hoc risk mitigation measures, such as equipment checks, warm-ups, and strict supervision, but these have not been integrated into a systematic framework. Risk identification, evaluation, and response are often based on experience or intuition rather than structured analysis. In addition, collaboration between various related parties, such as parents and medical personnel, still needs to be improved. This study concludes that more intensive socialization and training on risk management for school staff is needed. The development of specific and standardized risk management guidelines for sports activities in schools is also highly recommended to improve the safety and effectiveness of activities.